Relationship between Parenting Parents and Adolescent Independence - Nia Indrayati; Indra Ibrahim (Universitas Negeri Padang, 2019)
Independence requires an individual's readiness, both physical and emotional readiness without having to depend on others. to achieve independence, parenting can be a factor to help develop independence for adolescents. This study aims to examine the relationship of authoritative, authoritarian, indulgent and indifferent parenting with adolescent independence. This research is a descriptive correlational research with quantitative methods. Sampling in this study used stratified random sampling with a sample of 168 students. The research instruments used were questionnaires for parenting and independence of adolescents. The results revealed that (1) parenting mostly tended to apply authoritative parenting, (2) adolescent independence was in a fairly independent category, (3) there was a positive relationship with authoritative parenting with adolescent independence, (4) no parenting relationship authoritarian, (5) there is no relationship between indulgent parenting and adolescent independence, (6) there is no negative relationship between indifferent parenting parents and adolescent independence.